Implementation of the deconvolution method for signal peak detection in read-out ASIC. (December 2020) - Atkin, E; Azarov, D; Ivanov, P; Normanov, D; Serazetdinov, A; Shumikhin, V
Abstract: An application of the deconvolution method for signal peak detection in read-out ASIC for GEM detectors is described. Instead of usage of the conventional analog or digital peak detector, deconvolution technique to define the signal maximum was studied. In this case the digital data coming from the ADC are processed by a digital filter that deconvolves according to the pre-determined transfer function of the analog channel. Such processing allows to identify the signal peak values and also to provide reasonable pileup rejection. That enables higher rates of the incoming signals and reduces the amount of lost data. Combined with the analog channel employing 10-bit 25 MHz sampling rate ADC and 250 ns time constant 2nd-order shaper, the designed deconvolution block maintains peak detection accuracy within 9 LSBs. Time resolution of peak separation is 4 ADC sampling intervals or 100 ns.